2013
DOI: 10.1021/jp409067h
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Photothermal Conversion Efficiencies of Plasmonically Heated Gold Nanoparticles

Abstract: We report the light-to-heat energy transfer efficiencies of gold nanoparticles with variable sizes by assessing the temperature profiles of laser-activated particle suspensions in water. Gold nanoparticles with sizes ranging from 5 to 50 nm were synthesized by chemical reduction methods using sodium borohydride, sodium citrate, or hydroquinone as reducing agents. As-synthesized gold nanoparticle solution (1 mL) was loaded into a quartz cuvette and exposed to a CW green laser (532 nm). Heat input into the syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
311
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(328 citation statements)
references
References 44 publications
16
311
1
Order By: Relevance
“…It was demonstrated that the photothermal conversion efficiency of AuNP decreased from 0.8 to 0.65 when the diameter of AuNP increased from 5nm to 50 nm, see Fig.6 in Ref. 26. In consequence, even though single AuNP of larger diameter exhibits higher absorption efficiency, the collective photothermal effect is partly counteracted by the aforementioned factors.…”
Section: Discussionmentioning
confidence: 95%
“…It was demonstrated that the photothermal conversion efficiency of AuNP decreased from 0.8 to 0.65 when the diameter of AuNP increased from 5nm to 50 nm, see Fig.6 in Ref. 26. In consequence, even though single AuNP of larger diameter exhibits higher absorption efficiency, the collective photothermal effect is partly counteracted by the aforementioned factors.…”
Section: Discussionmentioning
confidence: 95%
“…The thermal energy is also transferred to the surrounding media through phonon-phonon interactions and results in the thermal effects observed [8]. The collective effect of exciting the surface plasmon using light and resulting in an increase in temperature of the surrounding media is known as light-to-heat conversion [27].…”
Section: Discussionmentioning
confidence: 99%
“…Since hemoglobin and water have the highest transmissivity in the NIR [7] this enables the stimulation of nanoparticles deeper into the tissue. When the nanoparticles are illuminated with laser light at a wavelength close to that of the surface plasmon, the electromagnetic energy absorbed heats up the electrons which thermalize with the lattice and the surrounding media [8,9]. This transfer of thermal energy can affect the surrounding tissue in several ways.…”
Section: Introductionmentioning
confidence: 99%
“…INTRODUCTION In recent years the absorption of radiation energy by NPs, light-to-heat conversion, heat dissipation and exchange with a surrounding material (medium), and following thermal and accompanied phenomena have become increasingly important topics in nanotechnology . Many reasons exist for this interest, including the applications of the light-to-heat conversion in nanoenergy [1][2][3][4][5][6][7][8][9][10][11][12], in photothermal laser nanomedicine [13][14][15][16] and catalysis [17,18], in laser processing of NPs (laser induced transformation of NP size, shape and structure) [19][20][21][22][23][24], etc. These advances in nanotechnology are based on the efficiency of light-to-heat conversion, thermal effects and the processes induced by the laser-NP interaction [1][2][3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Theoretical investigation of the light-to-heat conversion under action of radiation on NPs [1][2][3][4][5][6][7][8][9][10][11][12] is predominantly based on the description of the processes with single NP. The light-to-heat conversion with NP ensemble practically did not investigate and only a few general equations were formulated and the estimations were made.…”
mentioning
confidence: 99%